(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
In this article, the improvement and development of marketing activities in the enterprise, the provision of affordable and high-quality services to the population, the creation of economic and legal access, integration in the fields of production and other services, the creation of an effective mechanism for the state regulation of the production and trade sector, after-sales service improving the quality and timely delivery of services, being active in social networks, and promoting one's trade brand.